Steering the Ship of the Mind: Politics and Theology in the Nautical Expression of the Layered Mind in the Alfredian Translations - Ponirakis, Eleni (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
Following Gregory the Great, the Alfredian translator(s) make us of a metaphor where the mind is conceptualised as a ship, with Reason at the helm. The ship must navigate the dangerous waters of worldly temptation and at times is steered by God. The interchangeability of God and Reason at the helm suggests that Reason is, in some way, a God-like faculty. The ship of the mind is a common image in patristic texts, but its origin is Pre-Christian, and has its basis in Plato; in Phaedrus, rather than a ship, a chariot with headstrong horses is steered by the part of the mind known as the steersman of the soul (Emlyn-Jones and Preddy 2022, 416). This essay will attempt to trace the possible sources for the prevalence of this image in Gregory and in the Alfredian translations, with a particular focus on Hierdeboc or Pastoral Care, and the Old English Boethius. Although the Pastoral Care is a close rendering of the original, the Alfredian translator has added details which show an in-depth knowledge of contemporary sailing techniques. This essay will argue that the use of the ship of the mind metaphor not only taps into Christian Neoplatonic theology fashionable at the Carolingian court, but also styles King Alfred as a man of action, a competent sailor versed in the latest techniques of sailing and a competent hand on the tiller of state, where he is implicitly compared with God.